PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL BERBASIS GAME EDUKASI TERHADAP HASIL BELAJAR IPAS KELAS III DI SDN 07 TIUMANG - Estuhono Estuhono; Zumrotun Lutfiah; Orien Zikra Gefasya (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This research is motivated by students' lack of focus in participating in learning, it is said that students' interest in participating in the learning is low. This is caused by the learning material delivered being less interesting, because the class teacher delivers the material using the lecture method. This study aims to determine whether or not there is an effect of the use of educational game-based wordwall learning media on the learning outcomes of third-grade students in SDN 07 Tiumang. This research method is pre-experimental designs (non-designs) using the One-Group Pretest-Posttest Design. The population is all third-grade students of SDN 07 Tiumang. The sample in this study was 14 people consisting of 7 boys, 7 girls. The data collection technique in this study was a test in the form of objective questions. Based on the Paired Sample Test Hypothesis test, the results were 0.000 <0.05. It can be concluded that H0 is rejected Ha is accepted or the use of educational game-based wordwall learning media has an effect on the learning outcomes of third-grade students in SDN 07 Tiumang.